Development and content validation of a risk classification instrument - Marcia Beatriz Micha Ferreira de Oliveira; Lillian Caroline Fernandes; Ilana Eshriqui Oliveira; Ramon Antônio Oliveira; Flávio Rebustini; Ana Carolina Cintra Nunes Mafra; Eduarda Ribeiro dos Santos (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: Develop and validate the content of an instrument for patient risk classification in emergency services of Primary Health Care. Method: The study included two stages: item generation and content validity. A literature review and retrospective analysis of medical records were conducted to create the instrument items. The Content Validity Ratio (CVR) was used to assess agreement among judges during content validation. Results: In the first and second rounds, 75 and 71 judges validated the risk classification instrument, respectively. The minimum adherence score for the latent variable item based on the final number of judges was 0.22 and 0.18; thus, 52 items, divided into three classification categories (red, orange, and yellow), were retained. Conclusion: The instrument was considered valid regarding clarity, relevance, pertinence, and agreement regarding the severity indicated in the item.